Scientific Papers 2022
DOI: 10.52340/9789941488177
|View full text |Cite
|
Sign up to set email alerts
|

Დასავლეთ Საქართველოს Ავტოქთონური Ვაზის Ჯიშების Ფენოლური Ნაერთები

Abstract: მონოგრაფია ეძღვნება დასავლეთ საქართველოში გავრცელებული ვაზის ავტოქთონული ჯიშებისა და მისგან წარმოებული ღვინის ქიმიური შედგენილობის შესწავლას კვლევის თანამედროვე ინსტრუმენტული მეთოდების გამოყენებით. მათი ქიმიური შედგენილობის კორელაციური დამოკიდებულების განსაზღვრას ჯიშობრივ და ნიადაგურ-კლიმატურ ფაქტორებზე. მონოგრაფია საინტერესო იქნება საბუნებისმეტყველო და აგრარული, კვების პროდუქტების ტექნოლოგიის მიმართულებების სპეციალისტებისათვის, მსგავსი პროფილის საწარმოებში მომუშავე მუშაკების, დაინტერესებული პირების, ფერ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Our results correlated with data of Tsiakkas et al (2020) who found anthocyanin content of red wines from Cyprus ranged from 24.44±2.61 mg/dm 3 to 509.18±8.18 mg/dm 3 . Slightly higher levels of anthocyanins were found by Kharadze et al (2018) in a study of wines obtained from Georgian endemic varieties. The team found a variation in the anthocyanin content of the studied wines from 327.10 mg/dm 3 to 871.70 mg/dm 3 .…”
Section: Resultsmentioning
confidence: 97%
“…Our results correlated with data of Tsiakkas et al (2020) who found anthocyanin content of red wines from Cyprus ranged from 24.44±2.61 mg/dm 3 to 509.18±8.18 mg/dm 3 . Slightly higher levels of anthocyanins were found by Kharadze et al (2018) in a study of wines obtained from Georgian endemic varieties. The team found a variation in the anthocyanin content of the studied wines from 327.10 mg/dm 3 to 871.70 mg/dm 3 .…”
Section: Resultsmentioning
confidence: 97%
“…The antioxidant activity of oil samples was determined by the DPPH method. The results are given as 50% inhibition mg of sample, which is the amount of sample that inhibits the DPPH radical by 50% (the smaller the amount of sample is required for radical bleaching (mg), the higher the antioxidant activity is) (Gabour Sad et al., 2021 ; Kharadze, Djaparidze, et al., 2018 ; Kharadze, Japaridze, et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%